2015
DOI: 10.1371/journal.pone.0145209
|View full text |Cite
|
Sign up to set email alerts
|

Seroconversion of Hepatitis B Vaccine in Young Children in the Kassena Nankana District of Ghana: A Cross-Sectional Study

Abstract: BackgroundHepatitis B Virus (HBV) infection is an important public health problem that requires high priority efforts towards prevention and control. Active immunization is the single most important and effective preventive measure against HBV infection. As a protective measure, Ghana introduced the mass immunization program against hepatitis B infection in children in 2002 in her Expanded Programme on Immunization (EPI). This study evaluated seroconversion (the point in time when the amount of antibody in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 15 publications
5
23
1
Order By: Relevance
“…Figure clearly indicates that the protective levels waned with increasing age between 1 and 8 years old, the percentage of lower concentrations declined more rapidly and that of higher titres kept relatively stable, especially the rate of high‐responders without showing obvious increasing or decreasing trend, suggesting that high antibody levels may be maintained for longer. Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy . The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure clearly indicates that the protective levels waned with increasing age between 1 and 8 years old, the percentage of lower concentrations declined more rapidly and that of higher titres kept relatively stable, especially the rate of high‐responders without showing obvious increasing or decreasing trend, suggesting that high antibody levels may be maintained for longer. Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy . The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age …”
Section: Discussionmentioning
confidence: 99%
“…Some studies also demonstrated that antibody levels showed a significant decline in children after hepatitis B vaccination in infancy. [14][15][16] The decline of antibody concentrations may be associated with hepatitis B vaccine type, dosage, different vaccination programmes, physical quality and vaccination age. [17][18][19][20] Surprisingly, the proportion of protected anti-HBs titres slowly increased for children older than 8 years old, and the trend in antibody levels for children aged 9-16 declined compared to that in the 1-9 age groups, being >10 mIU/mL and of >100 mIU/mL, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The level of sero-conversion recorded in this study is very low when compared to studies from other countries within and outside Africa. Dassah S et al found 87.9%, 78.3% and 41.7% seroprotection after 0-6 months, 2-3 years and 3-5 yrs respectively after complete vaccination in Ghana [15], Chakraborty et al found 100% seroprotection (≥ 10 IU/L) in Bangladesh [16], Freitas da Motta et al found a seroconversion rate of 77% in preterm infants and 98% among full term infants 3 months after the third dose among vaccinated children in Brazil [17]. Other findings however shows similarity to ours revealing a decline of HBV vaccine protective levels with time after vaccination.…”
Section: Resultsmentioning
confidence: 97%
“…Lee, Chuanfang [23] postulated that the protection afforded by vaccination is long lasting even after antibody levels fall below 10 mIU/ml [23]. However, other studies has shown HBV prevalence despite the WHO established coverage and have recommended revaccination or booster doses [13][14][15][16][17][18][19][20][21].…”
Section: Resultsmentioning
confidence: 99%
“…There are many factors influencing the effectiveness of the vaccination. Some studies found that antibody levels showed a significant decline in children after HB vaccination in infancy [36][37][38]. One potential reason may be vaccination age [39,40].…”
Section: Discussionmentioning
confidence: 99%